Nursing care when facing adversity: commitments to resistance from academia (2010)
An analysis of the social and political context on health is presented, where there is evidence of the perverse effect that surrounds nursing today in Colombia, as a result of public policies and those of social security that the current neo liberal model has designed and implemented with the 100th Law dated 1993 and all its norms, which changed the right to health in a juicy merchandise for the "for profit" industry. In this context a first premise arises, which is argued to show how "the conditions under which we are providing nursing care in our market are awful and under high social, political and economic conflict, aspects that permeate family life, professional life, institutions and the world of nursing while putting at high risk the practice of health care, distancing it from being a public good. All achievements in terms of social recognition for the profession and for the practice and the discipline have also been placed at risk. All is forcing one to provide care in the "midst of adversity". As a result of such an environment, a second premise arises, that argues that "care characterized by the expropriation of its essence and of its subject is leading one to erode the essence of the role for a professional. These circumstances are expressed when we return to old ways of exclusion or alienation, or in the presence of new ways of expressing social action by the nursing professionals, who have been limited by the means available that generate a way of life in prolonged social, political and economic crisis, which is the way of life for Colombia today". The final part of the article contains a series of proposals that are geared to tackling the question: Where should we orient the governance of care? We start from the principle that the nursing world is not a for profit world. Nursing has a flagship of humanistic philosophy that promotes solidarity, that recognizes differences and the right to equality, among others; that is why it opts for the path of least resistance with three commitments: 1) redefining the meaning of care, 2) working towards an education and pedagogy in nursing that leverages liberties and 3) reconstructing the image of social nursing.